Association Between Selected Socio-Demographic Characteristics and Lower Urinary Tract Symptoms Among First-Time Mothers in Ogbomosho, Oyo State, Nigeria - Desmond, Zaki; S., Hashim Muhammad; G., Samuel-Udofia Cindy; Christian, Oduenyi; A., Karaga Mahmud; A., Iribom Sarratu T.; A., Adegoke Ayobami; M., Jeremiah Hope (Darul Yasin Al Sys, 2025)
Urinary incontinence and other lower urinary tract symptoms (LUTS) are common postpartum complaints that can significantly affect the quality of life of new mothers. Previous researchers have reported the influence of selected sociodemographic factors on LUTS in a general female population and multiparous women. However, there is limited literature on the association between these factors and LUTS among first-time mothers in this part of the world. Therefore, this study was designed to investigate the association between body mass index (BMI), age, mode of delivery, and the occurrence of LUTS among first-time mothers in Ogbomoso. Oyo State Nigeria. This cross-sectional survey was conducted among 70 consenting first-time mothers recruited from 3 major hospitals (or ante-natal clinics) in Ogbomoso, Oyo State. A sociodemographic form was used to assess sociodemographic characteristics of participants. Height was measured using a portable stadiometer, while weight was measured using a calibrated digital bathroom scale. The ICIQ-FLUTS, a structured questionnaire was used to assess LUTS among participants, this questionnaire assesses LUTS in three domains - filling, voiding, and incontinence domains. The Chi-square test was used to assess associations between variables, with level of significance set at 0.05. The mean age of participants was 31.26 ± 6.00 years (range: 22–45 years), mean BMI was 25.20 ± 4.21 kg/m² (range: 18.16–36.69 kg/m²), and mean weight was 69.48 ± 11.92 kg (range: 45–100 kg), 65.7% of participants delivered through spontaneous vaginal delivery, while 34.3% underwent cesarean section, and majority of (85.7%) had single births, whereas 14.3% had multiple births. BMI was significantly associated with both filling (χ² = 20.213, p = 0.017) and incontinence symptoms (χ² = 26.773, p = 0.002), but not with voiding symptoms (p = 0.431). No significant associations were observed between LUTS and age, mode of delivery, number of births, educational level, or occupation. A large proportion (75.7%) of the participants reported mild to moderate LUTS in the incontinence domain. Among first-time mothers, elevated BMI is a key risk factor for urinary filling and incontinence symptoms. These findings underscore the importance of incorporating weight management and pelvic floor rehabilitation into postpartum physiotherapy programs. Broader and longitudinal studies are recommended to validate these findings and guide effective intervention strategies.